A hybrid decision model for supplier selection in Online Fashion Retail (OFR). Issue 1 (2nd January 2022) - Kaushik, Vineet; Kumar, Ashwani; Gupta, Himanshu; Dixit, Gaurav
ABSTRACT: Multichannel retailing has caused significant disruption in the market. The major credit for this disruption belongs to online retailing, which is proliferating at a high pace. With the immense growth, the online fashion retail sector faces many challenges as well. The majority of these challenges are attributed to the inefficiency of suppliers to deliver the right products at the right time. Thus, supplier selection becomes an important parameter for the success of the online fashion retail industry. This study focused on supplier selection based on seven main criteria, which are Operational Competency, Product Attribute, Logistic Warehousing, Ethics, Status, Business Competencies, and Versatility. An integrated Best Worst Method (BWM) – VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) methodology was applied to prioritise the criteria and select the most feasible suppliers among available suppliers. Out of thirty-eight sub-criteria, those that got most preferences are Just in Time (JIT) Capabilities, Order Flexibility, Return Policies, Technical Soundness, Billing Flexibility. The results of the study disseminated theoretical and managerial implications that can be applied in online fashion retail.